Application of Virtual Reality Technology in College Physical Education Teaching and Training. Issue 4 (June 2019) - Liu, Hao
Abstract: With the continuous development of social science and technology, the application range of computers is wider and wider. The computer "virtual reality" technology is used in college sports training, which can enrich the content of physical education classrooms, update classroom teaching methods, and improve the quality and efficiency of physical education training. However, in the process of actual application, there are still some problems to be solved.